A Study of Hepcidin Levels and other Biochemical Parameters in Woman with Osteoporosis with Type 2 Diabetes Mellitus - Ahmed, Shuaib Yasin Ahmed; albayaty, noorhan khalid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Background: Diabetes mellitus (DM) could be regarded as a set of chronic metabolic disorders which have a common aspect of hyperglycemia. The resistance in the peripheral actions of insulin or impaired insulin secretion could be the reason  hepcidin which is a peptide hormone derived from liver, in systemic iron homeostasis is an essential regulator, and its lopsided production participates in the pathogenesis of iron disorders in spectrum. Osteoporosis often accompanies many diseases like ß-thalassemia, hemochromatosis, sickle liver diseases, cell disease and hemosiderosis featured by iron overload, evidences suggest that Iron overload and iron deficiency are suggested by evidences that they affect bone in a negative way, acting straightway on the cells of the bone. Aim: The current study aims to find the direct relationship between the levels of Hepcidin, DHVD3 and other parameters in Osteoporosis with type 2 DM, in a female patient Methods: This study involved 60 subjects divided to two groups 30 female Osteoporosis with type 2 DM patients and 30 healthy controls . Over the period from November 2021 until the end of June 2021, this study was conducted. The ranges of age were (40-55) years. All diabetic patients examined by an endocrinologist in the Al-Yarmouk Teaching Hospital and Al- Mahmudiya Hospital . They were treated  with oral anti-diabetic agents, mainly Metformin and Glibenclamide. The control subjects were referred to Laboratories Yarmouk Teaching Hospital, where all measurements were made. Control subjects were collected with glycemic control inclusion criteria when fasting serum glucose (FSG) < 100 mg/dL and HbA1c < 5.7%. BMI, Hb, hepcidin, Ferritin, Iron, DHVD3, Ca, PO4 were determined. Results: results was showed significant increase compared with control group in glycemic profile and lipid profile ,also, results showed a significant decrease compared with control group in Hb, Ferritin ,Iron , Vit D ,Ca , PO4  ,also the results showed a significant increase in hepcidin. Conclusion; By linking Ferritin, Iron vitamin D3 , Ca , PO4 deficiency and  Hepcidin overload to women was diagnosed Osteoporosis with T2DM which indicated vit D3 deficiency related  with hepcidin dysfunction. as an influencing factor on osteoarthritis women